PENERAPAN MICROSOFT OFFICE PADA ADMINISTRASI PERKANTORAN DI SMK IBRAHIMY 1 SUKOREJO - Septi Camelia Ulfa; Ika Indah Khasanah; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
Vocational High School (SMK) is one of the vocational education that receives attention from the government. This seminar aims to assess students' skills in using Microsoft Office programs, namely Microsoft Word, Microsoft Excel and Microsoft Power Point. For graduates who want to develop a career in the office sector, they should master the applications used in offices. SMK functions as a vocational school that organizes skills programs such as engineering, office, fine arts, restaurants, administration, and others, which can provide education, including hard skills that support professional skills. Currently, students must have the ability to run programs on Windows and the most commonly used programs such as Microsoft Office. SMK Ibrahimy is an Educational Institution under the auspices of the Salafiyah Syafiiyah Sukorejo Islamic Boarding School. This seminar can be used as evaluation material for vocational schools such as SMK Ibrahimy to improve the skills of their students.